Prerequisites and factors of pedagogical biographistics formation - Rozman Iryna (Бердянський державний педагогічний університет, 2020)
historical-pedagogical phenomenon requires clarification of its preconditions, that is the factors that determined its emergence and development. The emergence and formation of pedagogical biographistics as a separate, complex phenomenon was determined by a complex of interrelated social, socio-cultural, educational and scientific factors. There are prerequisites and factors for the formation of pedagogical biographistics. The prerequisites include the European traditions of the historical and biographical genre (the ages of Antiquity, the Middle Ages, the Renaissance, the Enlightenment, the Modern Times); Ukrainian biographical tradition (“chronicle of life” end of X-XVI centuries; cossack-chronicle the end of XVI-XVIII centuries; “empirical-scientific” of XIX century; imperial (Russian and Austro-Hungarian) and Western and Soviet 20-30 XX century and the biographical approach itself in history of philosophy and psychology, literary studies. The factors are separated into socio-political and state-political ones, which determined the ideological doctrines of the development of education and science; scientific and methodological directions; models; reflections of knowledge and research of social development (personalism, Freudism); development trends and institutional structure of historical-pedagogical science and stages of pedagogical thought development. A concentrated retrospective look at the development of the European biographical tradition allows us to draw a number of intermediate conclusions. The development of biography has always been conditioned by the existing socio-political and socio-cultural conditions and immediately responded to the next changes in social moods, ideological paradigms, worldview expectations. This circumstance and the general advancement of the humanities stimulated and depended on the modification of the types, species, genera of biographical works and their methodological foundations, which in the general dimension evolved between the artistic and scientific genres. The tradition of the Ukrainian biographical genre, its development and historical and pedagogical conditions, based on close interconnection, laid the foundation for the emergence, development and development of pedagogical biography in the last third of the XX – beginning of the XXI century.
Передумови та чинники формування педагогічної біографістики
Зародження і становлення педагогічної біографістики як окремого, складного феномену детермінувалося комплексом взаємопов’язаних суспільних, соціокультурних, освітньо-наукових факторів. Існують передумови та чинники формування педагогічної біографістики. До передумов належать європейські традиції історико-біографічного жанру (доба Античності, Середньовіччя, Відродження, Просвітництва, Новітнього часу); українська біографічна традиція («літописна житійна» кінця Х-ХVI ст., козацько-літописна кінця ХVI- ХVIІІ ст., «емпірично-наукова» ХІХ с.; імперська (російська і австро-угорська) та західноукраїнська та радянська 20-30 рр. ХХ ст. та саме біографічний підхід в історії філософії та психології, літературознавства. Чинники виокремлено на суспільно-політичні та державно-політичні, що визначило ідеологічні доктрини розвитку освіти і науки; науково-методологічні напрями; моделі; рефлексії пізнання і дослідження суспільного розвитку (персоналізм, фрейдизм); тенденції розвитку та інституційна структура історико-педагогічної науки та етапи розвитку педагогічної думки. Концентровано-ретроспективний погляд на розвиток європейської біографічної традиції дозволяє зробити низку проміжних висновків. Розвиток біографії завжди обумовлювався існуючими суспільно-політичними і соціокультурними умовами і відразу реагував на чергові зміни у суспільних настроях, ідейних парадигмах, світоглядних очікуваннях. Ця обставина та загальний поступ гуманітарних наук стимулювали й узалежнювали модифікацію типів, видів, родів біографічних творів і їхніх методологічних засад, які в загальному вимірі еволюціонували між художнім і науковим жанрами. Традиція українського біографічного жанру, її розвиток та історико-педагогічні умови, опираючись на тісний взаємозв’язок, заклали основу для виникнення, розвитку та становленню педагогічної біографістики в останній третині ХХ – на початку ХХІ століття.